HUBUNGAN STRES AKADEMIK DENGAN KESEJAHTERAAN PSIKOLOGIS SISWA KELAS XII SMA NEGERI 1 INDRALAYA UTARA - Azzahra, Merlina; Alrefi (IKIP Siliwangi, 2025)
This study aims to determine the relationship between academic stress and psychological well-being among 12th grade students at SMA Negeri 1 Indralaya Utara. The approach used is quantitative with a correlational method. The research sample consists of 103 students selected using simple random sampling. The instruments used are academic stress scales and psychological well-being scales that have been tested for validity and reliability. Data were analyzed using Pearson Product Moment correlation techniques. The results of the study indicate that most students are at a moderate (45%) and high (27%) level of academic stress, indicating that academic pressure is quite felt by students, although still within reasonable limits. On the other hand, the level of psychological well-being of students is dominated by the very high (45%) and high (23%) categories, indicating that the psychological condition of students tends to be positive. The analysis results show a significant negative correlation between academic stress and psychological well-being. This means that the higher the level of academic stress experienced, the lower the students' psychological well-being, and vice versa. This finding underscores the importance of addressing students' mental health through counseling services, stress management training, and support from the school environment and family.